Investigation into scavenging of sodium and ash deposition characteristics during co-combustion of Zhundong lignite with an oil shale semi-coke of high aluminosilicate in a circulating fluidized bed. (1st December 2019) - Liu, Zhuo; Li, Jianbo; Zhu, Mingming; Wang, Quanhai; Lu, Xiaofeng; Zhang, Yuanyuan; Zhang, Zhezi; Zhang, Dongke
Highlights: Scavenging of Na and ash deposition during co-combustion of ZD and SC investigated. Na-bearing minerals (e.g. Na2 SiO3 and NaAlSiO4 ) in fly ash decreased with SC addition. Na was retained in bottom ash, decreasing its fusion temperature with SC addition. Na2 SO4 and CaSO4 on probe surfaces promoted ash deposition during ZD combustion. Addition of SC enriched aluminosilicate in deposits, making them less sintered. Abstract: Scavenging of sodium and ash deposition characteristics during co-combustion of Zhundong lignite with an oil shale semi-coke in a circulating fluidized bed (CFB) were investigated. Zhundong lignite (ZD) and its blends with the semi-coke (SC) of 10 and 20 wt% were combusted in the CFB furnace at 950 °C. Two air-cooled probes were placed in the furnace chamber (P1 ) and at the cyclone outlet (P2 ), respectively, to simulate ash deposition. The bottom ash, fly ash and ash deposits on the probes were collected and analysed by using XRD, SEM-EDX, ICP-OES and laser particle analyser. Results show that the fly ash burning ZD was comprised of sub-micron particles and agglomerates enriched in CaSO4 and SiO2, with Na being NaAlSi3 O8, Na2 SiO3, Na2 Si2 O5 and NaAlSiO4 . When SC of high Si/Al was added, the fly ash was comprised of sub-micron particles with less agglomerates, where Na-bearing minerals were also evidently reduced. Likewise, the bottom ash was coarse-grained particles rich in SiO2, (Ca, Na)(Si, Al)4 O8 and CaSiO3 during ZD combustion but changed to SiO2, (Na, Ca)Al(Si, Al)3 O8 or NaAlSi3 O8 as SC was added, suggesting that Na was captured by SC and retained in the bottom ash. The deposit on P1 was enriched in Na2 SO4 and CaSO4 when ZD was burned but turned into coarse-grained particles rich in Ca/Na aluminosilicates while SC presented, showing a decreased sintering propensity. Likewise, the P2 deposit was of Ca/Na sulphates agglomerates, but became refractory SiO2, Ca sulphate and aluminosilicates as SC added. Ash deposition in CFB burning ZD is consequently mitigated with SC addition.